Anti‐SARS‐CoV‐2 IgG antibody levels among Thai healthcare providers receiving homologous and heterologous COVID‐19 vaccination regimens. Issue 4 (24th February 2022) - Kittikraisak, Wanitchaya; Hunsawong, Taweewun; Punjasamanvong, Somsak; Wongrapee, Thanapat; Suttha, Patama; Piyaraj, Phunlerd; Leepiyasakulchai, Chaniya; Tanathitikorn, Chuleeekorn; Yoocharoen, Pornsak; Jones, Anthony R.; Mongkolsirichaikul, Duangrat; Westercamp, Matthew; et al.
Abstract: Background: We examined SARS‐CoV‐2 anti‐spike 1 IgG antibody levels following COVID‐19 vaccination (AstraZeneca [AZ], Sinovac [SV], Pfizer‐BioNTech [PZ]) among Thai healthcare providers. Methods: Blood specimens were tested using enzyme‐linked immunosorbent assay. We analyzed seven vaccination regimens: (1) one dose of AZ or SV, (2) two doses of homologous (2AZ, 2SV) or heterologous (1AZ + 1PZ) vaccines, and (3) three doses of heterologous vaccines (2SV + 1AZ, 2SV + 1PZ). Differences in antibody levels were assessed using Kruskal–Wallis statistic, Mann–Whitney test, or Wilcoxon matched‐pairs signed‐rank test. Antibody kinetics were predicted using fractional polynomial regression. Results: The 563 participants had median age of 39 years; 92% were female; 74% reported no underlying medical condition. Antibody levels peaked at 22–23 days in both 1AZ and 2SV vaccinees and dropped below assay's cutoff for positive (35.2 binding antibody units/ml [BAU/ml]) in 55 days among 1AZ vaccinees compared with 117 days among 2SV vaccinees. 1AZ + 1PZ vaccination regimen was highly immunogenic (median 2279 BAU/ml) 1–4 weeks post vaccination. 2SV + 1PZ vaccinees had significantly higher antibody levels than 2SV + 1AZ vaccinees 4 weeks post vaccination (3423 vs. 2105 BAU/ml; p ‐value < 0.01), and during weeks 5–8 (3656 vs. 1072 BAU/ml; p ‐value < 0.01). Antibodies peaked at 12–15 days in both 2SV + 1PZ and 2SV + 1AZ vaccinees, but those of 2SV + 1AZ declined more rapidly and dropped below assay's cutoff in 228 days while those of 2SV + 1PZ remained detectable. Conclusions: 1AZ + 1PZ, 2SV + 1AZ, and 2SV + 1PZ vaccinees had substantial IgG levels, suggesting that these individuals likely mounted sufficient anti‐S1 IgG antibodies for possible protection against SARS‐CoV‐2 infection.